2004
DOI: 10.1016/j.devcel.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A Role of VAMP8/Endobrevin in Regulated Exocytosis of Pancreatic Acinar Cells

Abstract: Despite our general understanding that members of the SNARE superfamily participate in diverse intracellular docking/fusion events, the physiological role of the majority of SNAREs in the intact organism remains elusive. In this study, through targeted gene knockout in mice, we establish that VAMP8/endobrevin is a major player in regulated exocytosis of the exocrine pancreas. VAMP8 is enriched on the membrane of zymogen granules and exists in a complex with syntaxin 4 and SNAP-23. VAMP8-/- mice developed norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
232
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(254 citation statements)
references
References 51 publications
18
232
3
Order By: Relevance
“…6; and data not shown). Western blotting of the Percoll gradient fractions for the secretory granule SNARE Vamp8 (Wang et al, 2004;Weng et al, 2007) confirmed that secretory granules were enriched in fraction 3 of the Percoll gradient. We also detected some Vamp8 in lighter fractions toward the top of the Percoll gradient.…”
Section: Sdmg1 Is a Component Of Pancreatic Secretory Granulesmentioning
confidence: 72%
See 3 more Smart Citations
“…6; and data not shown). Western blotting of the Percoll gradient fractions for the secretory granule SNARE Vamp8 (Wang et al, 2004;Weng et al, 2007) confirmed that secretory granules were enriched in fraction 3 of the Percoll gradient. We also detected some Vamp8 in lighter fractions toward the top of the Percoll gradient.…”
Section: Sdmg1 Is a Component Of Pancreatic Secretory Granulesmentioning
confidence: 72%
“…The expression of Sdmg1 in the exocrine secretory cells in the pancreas, salivary gland, and mammary gland, and the localization of Sdmg1 to pancreatic secretory granules, bears some resemblance to the expression and subcellular localization of the Vamp8 SNARE (Wang et al, 2004;Weng et al, 2007). Expression of Vamp8 and Sdmg1 are also both up-regulated in a male-specific manner during embryonic gonad development (Best et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Regarding the secretory signaling pathway and machinery, CCKAR (Fig. 5I), VAMP8 -a SNARE protein associated with ZG whose function is crucial for secretion (36) (Fig. 5G), and syntaxin 4 -a membrane protein of pancreatic acinar cells (36) - (Fig.…”
Section: Cells Having Activated the Acinar Gene Expression Program DImentioning
confidence: 99%